2017
DOI: 10.3847/1538-4357/aa86b5
|View full text |Cite
|
Sign up to set email alerts
|

The Frequency-dependent Damping of Slow Magnetoacoustic Waves in a Sunspot Umbral Atmosphere

Abstract: High spatial and temporal resolution images of a sunspot, obtained simultaneously in multiple optical and UV wavelengths, are employed to study the propagation and damping characteristics of slow magnetoacoustic waves up to transition region heights. Power spectra are generated from intensity oscillations in sunspot umbra, across multiple atmospheric heights, for frequencies up to a few hundred mHz. It is observed that the power spectra display a power-law dependence over the entire frequency range, with a sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 89 publications
4
18
0
Order By: Relevance
“…3a point towards a universal sunspot characteristic for waves detected in chromospheric spectral lines. A recent observational examination of the spectral power slopes for an entirely different sunspot, using ground-based images obtained in the Ca II K and Hα line cores, found similar spectral gradients (within the 6 − 17 mHz spectral range) to those presented here 42 . These gradients are steeper than both the f −1 and f −5/3 relationships that would be expected for granulation (i.e., pink) noise patterns 46 and the Kolomogorov inertial range 47 , respectively.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…3a point towards a universal sunspot characteristic for waves detected in chromospheric spectral lines. A recent observational examination of the spectral power slopes for an entirely different sunspot, using ground-based images obtained in the Ca II K and Hα line cores, found similar spectral gradients (within the 6 − 17 mHz spectral range) to those presented here 42 . These gradients are steeper than both the f −1 and f −5/3 relationships that would be expected for granulation (i.e., pink) noise patterns 46 and the Kolomogorov inertial range 47 , respectively.…”
supporting
confidence: 80%
“…To calculate the spectral slopes corresponding to regions II and III, maximum-likelihood fitted gradients are computed for each of the 101 spectral energies across the chromospheric umbra. Often linear lines of best fit are established to determine the spectral slopes of Fourier power spectra 42 . However, the weighted least-squares minimisation process assumes that the data to be fitted are normally (Gaussian) distributed 20 , which may not necessarily be the case, especially when the periodogram of a stationary, linear stochastic process naturally follows a χ 2 2 distribution 43,44 .…”
mentioning
confidence: 99%
“…They related such highfrequency modes at coronal heights to perturbations at photospheric umbra. Krishna Prasad et al (2017) reported frequencies around 13 mHz using IRIS 2796 Å in chromospheric sunspot umbra. We note that the observed high frequency around 11 mHz is close to two times that of the dominant (fundamental) frequency at around 5.56 mHz, and hence is similar to the second harmonics.…”
Section: Discussionmentioning
confidence: 99%
“…A large variety of different magnetohydrodynamic (MHD) wave modes are theoretically predicted, and indeed observed, in solar magnetic structures ranging from large sunspots extending over several Mm, down to very small magnetic elements at the limit of spatial resolution on current solar telescopes [1][2][3][4][5][6][7][8][9][10]. Magnetic fields connect different heights in the solar atmosphere, thus MHD waves propagating along them [11] can play a major role in supplying the energy budget to the upper layers of the solar atmosphere [12][13][14][15][16][17]. When particular magnetic field geometries and local physical conditions are met, propagating MHD waves of one type can be converted into another (e.g.…”
Section: Introductionmentioning
confidence: 99%